La estimulación temprana y su incidencia en el desarrollo del lenguaje oral de las niñas y niños del nivel I de 2 y 3 años de edad de los centros infantiles del buen vivir El Ángel de María y Gotitas de Cristal de la ciudad de Quito del periodo 2012-2013 - Rivera Pillasagua, Mercedes Celia (2014)
The present work makes reference to "THE EARLY STIMULATION AND ITS INCIDENCE IN THE DEVELOPMENT OF THE ORAL LANGUAGE OF THE GIRLS AND CHILDREN OF THE LEVEL OF 2 AND 3 YEARS OF AGE OF THE INFANTILE CENTERS OF THE GOOD one to LIVE "ANGEL DE MARÍA" AND "DROPS OF GLASS "OF THE you TAKE CARE OF I REMOVE OF PERIÓDO 2012-2013." Elaborated according to the regulation of the National University of Loja. He/she thought about for the investigation a general objective: To make aware the family parents, mothers, educating and teachers parvularias about the importance of the Early Stimulation in the Development of the Oral Language of the children and level girls I, 2 and 3 years of age. It was used methods like: Scientific, Analytic. Synthetic, Deductive, Inductive, Synthetic, I Model Statistical, besides technical as the observation, the survey directed to the teachers and family parents to know if they carry out activities of Early Stimulation in the daily day and the test of Zimmerman to determine the development of the Oral Language. Analyzed the results of the survey applied to the educational ones the teacher's 67% frequently carry out activities of Early Stimulation, 33% doesn't make it. 100% of teachers carries out activities of Early Stimulation as: they are songs, games, literatures plastic infantile and technical grafo. 67% of family parents yes they not know the importance of the Early Stimulation and 33%. According to Test of Zimmerman applied the 2 year-old children / ace, 50% of children is located in a normal level of development of Oral Language, 33% in excellent level and 17% in low level